The Nexus Between Black-Scholes-Merton Option Pricing and Risk: A Case of Ghana Stock Exchange - Antwi Baafi, Joseph; Sarkodie, Eric Effah (Archives of Business Research, 2022)
Even though option pricing and its market activities are not new, in Ghana the idea of trading options is yet to be realized. One popular method in pricing options is known as Black-Scholes-Merton option pricing model. Even though option pricing activities are not currently happening on the Ghana Stock Exchange, authors looked at the possibilities and preparedness of the GES to start trading such financial instrument. The main objective of this study therefore was to know how Black-Scholes-Merton model could be used to help in appropriate option value and undertake a risk assessment of stocks on the exchange. This study basically used the black-Scholes formula in calculating the call and put option prices for 28 companies listed GES. The results showed that the price of call option for 18 out of 28 listed stocks showed a value of zero. Again, only seven (7) companies had a value for both call and put options. This means stocks of 21 companies cannot be an underlying asset for trading financial derivatives. Reason for this performance of stock is due to low volatility. The study recommends that policies to increase volatility on the stock market should be put in place in other to make option pricing possible.